2002
DOI: 10.1067/mva.2002.121128
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of chronic venous ulcers on the basis of clinical, etiologic, anatomic, and pathophysiologic criteria and air plethysmography

Abstract: Leg ulcers associated with CVI have a high rate of recurrence. Ulcer recurrence is significantly increased in patients with DVI and in patients who do not have venous abnormalities corrected surgically. The VFI obtained from APG is useful in the prediction of increased risk for recurrence, particularly in association with anatomic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 17 publications
(15 reference statements)
4
71
2
6
Order By: Relevance
“…Some patients are treated by a superfi cial venous operation alone, but McDaniel et al 5 reported that chronic venous ulcers tended to recur more in patients with deep venous insuffi ciency than in those without. Makarova et al 6 showed that the presence of deep venous insuffi ciency is a determining factor in the progress of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Some patients are treated by a superfi cial venous operation alone, but McDaniel et al 5 reported that chronic venous ulcers tended to recur more in patients with deep venous insuffi ciency than in those without. Makarova et al 6 showed that the presence of deep venous insuffi ciency is a determining factor in the progress of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…However, risk factors for ulcer recurrence (other than presence of postthrombotic disease) have been identified and some may be helpful (eg, residual iliofemoral vein obstruction; residual deep incompetence, particularly axial deep reflux; residual or recurrent superficial reflux; and persistent venous hypertension). [27][28][29][30] Discussion highlights. There are many proposed clinical risk factors, which need clarification of their role in progression of the disease.…”
Section: Critical Issuementioning
confidence: 96%
“…24 This prognostic factor ''initial lesion area'' allows us to identify patients in whom evolution can be worst, which can help us raise more adequate treatment in patients with poor prognosis. Unfortunately, recurrence of the ulcer is common 33,34 and many patients suffer multiple episodes of ulceration. 35 The primary method of preventative treatment involves providing compression of between 35 and 45 mm Hg at the ankle.…”
Section: Discussionmentioning
confidence: 99%